The ground effects of severe space weather. Issue 4 (1st August 2018) - Beggan, Ciarán; Wild, Jim; Gibbs, Mark
Abstract : Ciarán Beggan, Jim Wild and Mark Gibbs on a meeting that explored the effects of major solar activity on Earth. Abstract : Ciarán Beggan, Jim Wild and Mark Gibbs report from an RAS meeting in March that explored the potentially devastating effects of major solar activity on Earth.